Iterative Learning Control: Brief Survey and Categorization - Hyo-Sung Ahn; YangQuan Chen; Moore, K.L. (IEEE transactions on systems, man and cybernetics. Part C, Applications and reviews, 2007)
In this paper, the iterative learning control (ILC) literature published between 1998 and 2004 is categorized and discussed, extending the earlier reviews presented by two of the authors. The papers includes a general introduction to ILC and a technical description of the methodology. The selected results are reviewed, and the ILC literature is categorized into subcategories within the broader division of application-focused and theory-focused results.